The Perception of Muslim Millennial Traveler’s Towards Halal Tourism - Supaijo Supaijo; Deki Fermansyah (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2019)
The main purpose of this paper is to explore the perceptions of muslim millenial traveler’s towards halal tourism in indonesia. It also investigates the extent to which muslim millennial traveler’s are willing to purchase certain types of halal products and services in halal tourism. Qualitative data were collected by conducting 150 semi-structured interviews with muslim millenneal traveler’s in three province in indonesia: nusa tenggara barat, sumatera barat and aceh. Four major aspects (access, communications, environment and services) are identified that describe the perceptions of muslim millennial traveler’s towards halal tourism. This paper also provides some suggestions for stake holders on how best to enggaged for muslim millenneal traveler’s. This paper explores the perceptions of muslim millennial traveler’s towards halal tourism which is totally new research in destination marketing. It provides some original insights in to the interactions between the religion of islam and tourism.